2018
DOI: 10.1021/acsbiomaterials.8b00570
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Fluoride under Dose Range of 2.4–24 μM, a Promising Osteoimmunomodulatory Agent for Vascularized Bone Formation

Abstract: Fluoride has essential effects on bone physiological activity and is widely used in bone biomaterials modification. However, this beneficial effect is highly related to the dose range and improper dosing can lead to pathological conditions such as fluorosis of bone. Therefore, this study first investigated the dose dependent effect of fluoride on bone regeneration. In the range of 0.24–240 μM, in vivo vascularized bone formation can be achieved via fine-tuning the fluoride concentration, and the peak osteogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Previous studies have reported that macrophage polarization plays a key role in fracture healing. 27,28 It is welldemonstrated that M2 macrophages are closely related with accelerated clavicle fracture healing in patients with traumatic brain injury (TBI). 29 To verify that the accelerated femoral fracture is also associated with macrophage polarization in TBI mice, we induced concomitant TBI and femoral fracture as well as isolated femoral fracture in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that macrophage polarization plays a key role in fracture healing. 27,28 It is welldemonstrated that M2 macrophages are closely related with accelerated clavicle fracture healing in patients with traumatic brain injury (TBI). 29 To verify that the accelerated femoral fracture is also associated with macrophage polarization in TBI mice, we induced concomitant TBI and femoral fracture as well as isolated femoral fracture in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Their hard metal surfaces were prone to form scar tissue via activating cells into fibrillar subtypes in the absence of exogenous signals, unlike soft materials such as hydrogels [ [18] , [19] , [20] ]. Therefore, numerous studies have attempted to inhibit or even eliminate this unsatisfactory inflammatory-fibrous response to guarantee the proper functioning of the metal material [ [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fluoride ions at specific concentration have been shown to modulate the macrophage inflammatory response. For instance, a recent study showed that fluoride ions at ultralow and ultrahigh concentrations can activate RAW264.7 macrophages polarized to the M1 phenotype with increased expression of pro-inflammatory genes (interleukin 6 (IL-6) and IL-1β), while a dose range of fluoride ions between 2.4 and 24 µM effectively downregulates M1 markers (inducible nitric oxide synthase (iNOS)) and upregulates M2 markers (arginase (ARG)), which could induce a beneficial osteoimmune environment for bone regeneration [17]. Nevertheless, other reports showed that micromolar fluoride concentrations can reduce the macrophage population and significantly increase the secretion of pro-inflammatory cytokines [18,19].…”
Section: Introductionmentioning
confidence: 99%